DO FINTECH INNOVATIONS MATTER FOR THE EFFICIENCY AND STABILITY OF BANKS IN SOUTH AFRICA? - Mhlongo, Njabulo; Kunjal, Damien; Muzindutsi, Paul-Francois (Universitas Nahdlatul Ulama Surabaya, 2025)
Innovations in financial technology (fintech) are driving a rapid transition in the global banking system, offering more efficient, tailored, and cost-effective solutions that challenge traditional banking methods. In South Africa, the stability of the banking sector is critical to economic growth because it provides capital, manages risks, and facilitates transactions. This study investigates the impact of fintech innovations on the efficiency and stability of banks listed on the Johannesburg Stock Exchange (JSE) between 2000 and 2023 using a panel data approach. The results suggest that Fintech has a positive influence on operational efficiency, notably through mobile transactions. However, Fintech has no effect on banking sector stability, with traditional capital structures outweighing Fintech innovations. These findings emphasize the dual nature of Fintech’s impact; that is, it fosters efficiency improvements but also introduces new risks by disrupting traditional banking services through more convenient and cost-effective alternatives. As this landscape evolves, adaptive regulatory frameworks are needed to balance the benefits of technological advancements with the need for adequate protection within the banking sector.